A 1.2GPa-grade hydrogen embrittlement-resistant cold-formed automobile steel and a preparation method thereof

CN117867385BActive Publication Date: 2024-12-17ANGANG STEEL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311787507.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-25
Publication Date
2024-12-17
Estimated Expiration
2043-12-25

AI Technical Summary

Technical Problem

The existing 1.2GPa-grade ultra-high strength automotive steel has poor forming performance and hydrogen embrittlement problems during the cold forming process, making it difficult to take into account high strength and high plasticity, and fail to meet the diversified, multi-spec and small batch orders in the automotive industry. need.

Method used

Using an alloy design of 1.2GPa grade hydrogen embrittlement-resistant cold forming automotive steel, containing C, Mn, Si, Al, Ni, Mo, P, S, N, Mg, Ti, V and other elements, smelting through electric furnaces, Medium-thin slab continuous casting, continuous rolling, pickling and cold rolling, quenching and partitioning continuous annealing or hot-dip galvanizing technology, control microstructure to be 10%-30% ferrite, 60%-80% martensite, 5%-20 % residual austenite achieves high strength, hydrogen embrittlement resistance and high pore expansion properties of steel.

Benefits of technology

It has achieved high yield strength, tensile strength and ductility of steel, met the diversified needs of automotive steel, reduced production costs and carbon emissions, and adapted to the green and low-carbon product design of the automotive industry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117867385B_ABST
    Figure CN117867385B_ABST
Patent Text Reader

Abstract

The invention provides a 1.2GPa-grade hydrogen embrittlement-resistant cold-formed automobile steel and a manufacturing method thereof. The steel plate components are calculated by weight percentage as follows: C: 0.20%-0.30%, Mn: 2.0%-3.5%, Si: 0.5%-2.5%, Al: 0.7%-7.0%, Ni: 0.05%-0.80%, Mo: 0.05%-0.80%, P≤0.01%, S≤0.01%, N≤0.005%, Mg: 0.005%-0.50%, Ti: 0.01%-0.50%, V: 0.01%-0.50%, 5≤Al / Si≤10, 5≤Mo / Ti≤10, and the balance is Fe and unavoidable impurities. The steel production method comprises smelting, medium-thin slab continuous casting and rolling, pickling and cold rolling, quenching and partitioning, and skin-passing. The steel of the present invention can realize a set of alloy systems to meet the diversified product requirements of 1.2GPa level due to the special design of composition and process, that is, one steel for multiple uses. The steel of the present invention has a yield strength of ≥900MPa, a tensile strength of ≥1200MPa, an elongation of A80 after fracture of ≥16.0%, a hole expansion rate of ≥30%, and a density of 6.5-7.5g / cm 3 The steel plates were prestressed by 180° U-bending and immersed in 0.5 mol / L HCl solution for 14 days without delayed fracture.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cold-rolled automobile steel and relates to a 1.2 GPa-level hydrogen embrittlement-resistant cold-formed automobile steel and a preparation method thereof. Background Art

[0002] Traditional cold-formed quenched and partitioned ultra-high strength automotive steel contains multiphase structures such as ferrite, tempered martensite and austenite. A large amount of austenite will be converted into fresh martensite during the cold forming process, and residual stress will exist inside the product, which makes QP steel suffer from serious hydrogen embrittlement (hydrogen-induced delayed fracture) during the service of parts, and the hydrogen-induced delayed fracture sensitivity of ultra-high strength steel will increase significantly with the increase of strength level. Because this phenomenon seriously affects the normal service of parts, the delayed fracture phenomenon of 1.2GPa-grade cold-formed ultra-high strength QP steel has received great attention from manufacturers and users. The steel industry is actively promoting energy conservation, environmental protection and green transformation and development, and 1.2GPa-grade QP steel products have the characteristics of diversified parts, diversified user needs, multiple product specifications and special needs for small batch orders. Therefore, the development of green and low-carbon QP steel products for automobiles, that is, one steel multi-purpose alloy design and short-process low-cost preparation technology, can not only meet the special needs of the automotive industry with multiple parts, diversified user needs, multiple specifications and small batch orders, but also is an effective measure for steel companies to improve their competitiveness, and has become a research hotspot for major steel suppliers. Based on the above research status, it is urgent to solve the problems of poor forming performance and hydrogen embrittlement of automotive high-strength steel, and at the same time adapt to the design of green and low-carbon products of automotive high-strength steel. Based on the above research status, it is urgent to solve the problems of poor forming performance and hydrogen embrittlement of ultra-high-strength quenching and partitioning steel, and at the same time adapt to the design of green and low-carbon products of automotive high-strength steel.

[0003] Patent document CN112095046B discloses an ultra-high strength cold-rolled DH1180 steel and a preparation method thereof, wherein the main chemical components are: C: 0.18% to 0.25%, Mn: 1.8% to 2.8%, Si: 0.5% to 1.4%, Al: 0.02% to 1.4%, Cr: 0.03% to 0.60%, Mo: 0.04% to 0.40%, Ti: 0.002% to 0.10%, P≤0.03%, S≤0.03%, V≤0.05%, Nb≤0.1%, and the rest are Fe and unavoidable impurities. The invention adopts a cold rolling-continuous annealing production process to produce ultra-high strength cold-rolled DH1180 steel. The product of the invention has excellent hydrogen embrittlement resistance and cold bending performance, but the product has poor plasticity and is difficult to meet the problem of ultra-high strength, high plasticity and hydrogen embrittlement resistance.

[0004] Patent document CN113403550A discloses a high plasticity and fatigue-resistant cold-rolled hot-dip galvanized DH1180 steel plate and a preparation method thereof, wherein the main chemical components are: C: 0.16% to 0.25%, Mn: 1.8% to 2.6%, Si: 0.2% to 0.8%, Al: 0.50% to 1.50%, Cr: 0.10 to 0.60%, Cu: 0.10 to 0.70%, P≤0.01%, S≤0.01%, N≤0.003%, Nb: 0.005% to 0.15%, V: 0.005% to 0.15%, Ti: 0.005% to 0.15%, and the remainder is Fe and other inevitable impurities. This invention adopts the cold rolling-hot dip galvanizing production process to produce high plasticity and fatigue resistant cold rolled hot dip galvanized DH1180 steel plate. This product exhibits excellent fatigue resistance and high hole expansion. However, this product does not take into account the hydrogen embrittlement problem of ultra-high strength steel, and it is difficult to meet the requirements of ultra-high strength, high plasticity and hydrogen embrittlement resistance.

[0005] The above-mentioned ultra-high strength steels all have a tensile strength of 1.2 GPa, which are used for resistance to hydrogen embrittlement or for obtaining better service and forming properties, respectively. Their products are not related or hydrogen-induced delayed cracking performance is not involved. Summary of the invention

[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a 1.2GPa-grade hydrogen embrittlement-resistant cold-formed automobile steel and a production method thereof. The present invention realizes the multi-purpose and lightweight design and development of automobile high-strength quenching and partitioning steel with a short process and low-cost process path and an extremely cost-reducing alloy design, while taking into account the personalized needs of hydrogen embrittlement resistance, high plasticity and high hole expansion, providing a reliable technical solution for automobile manufacturers and steel companies.

[0007] The object of the invention is achieved in this way:

[0008] A 1.2 GPa grade hydrogen embrittlement resistant cold-formed automobile steel comprises the following components by weight percentage: C: 0.20%-0.30%, Mn: 2.0%-3.5%, Si: 0.5%-2.5%, Al: 0.7%-7.0%, Ni: 0.05%-0.80%, Mo: 0.05%-0.80%, P≤0.01%, S≤0.01%, N≤0.005%, Mg: 0.005%-0.50%, Ti: 0.01%-0.50%, V: 0.01%-0.50%, and the balance is Fe and unavoidable impurities.

[0009] Furthermore, in the components, 5≤Al / Si≤10, 5≤Mo / Ti≤10.

[0010] Furthermore, the steel plate has a yield strength of ≥900 MPa, a tensile strength of ≥1200 MPa, an A80 elongation after fracture of ≥16.0%, a hole expansion rate of ≥30%, and a density of 6.5-7.5 g / cm 3 The steel plate was prestressed by 180° U-bending and immersed in a 0.5 mol / L HCl solution for 14 days without delayed fracture; the thickness of the steel plate was 1.0 mm to 2.0 mm.

[0011] Furthermore, the microstructure of the steel plate is, by volume percentage, 10% to 30% ferrite, 60% to 80% martensite, and 5% to 20% retained austenite, the total being 100%; the retained austenite is in a film-like form, with a grain size between 0.05 μm and 0.50 μm, and the film-like residual austenite is mainly distributed between the martensite laths.

[0012] Furthermore, 10. The hot-rolled microstructure of the hot-rolled process is composed of 30% to 60% ferrite, 20% to 50% pearlite, 5% to 20% bainite, and 1% to 5% cementite by volume percentage, and the total is 100%.

[0013] The reasons for the alloy design of the present invention are as follows:

[0014] C: Carbon element ensures the strength requirement of steel through solid solution strengthening. Sufficient carbon element helps to stabilize austenite, thereby improving the formability of steel and facilitating the design of one steel for multiple uses. If the content of C element is too low, the mechanical properties of the steel in the present invention cannot be obtained; if the content is too high, the steel will become brittle and there is a risk of hydrogen-induced delayed fracture. Therefore, in the present invention, the content of C element is controlled to 0.20% to 0.30%.

[0015] Mn: Manganese is an austenite stabilizing element in steel. It can expand the austenite phase area and reduce the critical quenching rate of steel. At the same time, it can also refine the grains and help to improve the strength through solid solution strengthening. If the Mn content is too low, the supercooled austenite is not stable enough, which reduces the processing properties such as plasticity and toughness of the steel plate; if the Mn content is too high, the welding performance of the steel plate will deteriorate and the production cost will increase, which is not conducive to industrial production. Therefore, in the present invention, the Mn content is controlled to 2.0% to 3.5%.

[0016] Si: Silicon has a certain solid solution strengthening effect in ferrite, ensuring that the steel has sufficient strength. At the same time, Si can also inhibit the decomposition of residual austenite and the precipitation of carbides, reducing inclusions in the steel. In the present invention, the Si element is used in combination with the Al element, and the design concept of replacing silicon with aluminum can significantly improve the surface quality of the steel. If the Si element content is too low, it will not have a strengthening effect; if the Si element content is too high, it will reduce the surface quality and welding performance of the steel plate. Therefore, in the present invention, the Si element content is controlled to 0.5% to 2.5%.

[0017] Al: The density of aluminum is much lower than that of Fe. Adding an appropriate amount of Al to steel can significantly reduce the density of steel, which is conducive to the lightweight development of steel. At the same time, Al has an antioxidant effect. Adding it in combination with Si can effectively improve the surface quality of steel, which is conducive to the design of one-steel-multiple-purpose products. In addition, Al can also inhibit the decomposition of residual austenite and the precipitation of carbides, and accelerate bainite transformation to improve the coordinated deformation ability. Too high Al content will not only increase production costs, but also lead to difficulties in continuous casting production. When the aluminum content is too low, low-density material design cannot be achieved. Therefore, in the present invention, the content of Al is controlled within the range of 0.7% to 7.0%.

[0018] Ni: Nickel is an important element for improving the welding performance of steel. The addition of Ni is beneficial to improving the toughness of the weld, especially the low-temperature impact toughness, reducing the brittle transition temperature, and helping to improve the material's hydrogen embrittlement resistance. The present invention controls the Ni content to be within the range of 0.05% to 0.80%.

[0019] Mo: Mo is a strengthening element in steel, which helps to stabilize the residual austenite and has a significant effect on improving the hardenability of steel. Mo and Ti can form a large number of TiMoC precipitates, which is conducive to making the diffuse hydrogen in the steel dispersed and reducing the aggregation of diffuse hydrogen, so that both high strength and hydrogen embrittlement resistance can be taken into account. The present invention controls the content of Mo element in the range of 0.05% to 0.80%.

[0020] P: P is a harmful element in steel, which is very easy to segregate to the grain boundary and seriously reduce the plasticity and deformation performance of the steel. The lower its content, the better. Considering the cost, the content of P in the present invention is controlled to P≤0.01%.

[0021] S: S is a harmful element in steel. Sulfur and manganese are easily combined to form MnS inclusions. After rolling and deformation, the transverse properties of the material will be significantly reduced, which seriously affects the formability of the steel. The lower the content, the better. Considering the cost, the content of S in the present invention is controlled to S≤0.01%.

[0022] N: N element easily reacts with Ti to precipitate large TiN particles, which act as crack sources during deformation and are detrimental to the anti-hydrogen embrittlement performance. Therefore, the N element content in the steel must be strictly controlled. The present invention controls the N content to N≤0.005%.

[0023] Mg: Magnesium is a good deoxidizer, desulfurizer and spheroidizer in steel. Mg can reduce the number of inclusions in steel, reduce their size, make their distribution uniform and improve their morphology. A small amount of magnesium can improve the carbide size and distribution of DH steel, promote the fine and uniform carbide particles, and also help to achieve low-density material design. In order to control production costs, the Mg content is controlled at 0.005% to 0.50% in the present invention.

[0024] Ti: A small amount of Ti element can refine the grain size, and the precipitate can pin dislocations to delay the expansion of crack sources, and significantly improve the strength and toughness of the material. When used in combination with Mo, it helps to disperse the diffuse hydrogen in the steel and reduce the aggregation of diffuse hydrogen, thereby taking into account both high strength and hydrogen embrittlement resistance. In the present invention, the Ti element content is controlled at 0.01% to 0.50%.

[0025] V: Microalloying element vanadium mainly exists in the form of VC, which improves the strength and fatigue resistance of the material through fine grain strengthening and dispersion strengthening. In the hot-dip galvanizing annealing heating process, undissolved VC particles can pin the ferrite grain boundary, thereby playing a role in refining the grains; when the annealing temperature increases to the two-phase region, the VC dissolution temperature is low, so it is fully dissolved in the matrix, and the solid solution C atoms are enriched in the austenite to improve its stability; during the annealing process, the VC in the ferrite will re-precipitate, thereby producing obvious precipitation strengthening. Therefore, in the present invention, the V element content is controlled at 0.01-0.50%.

[0026] The second technical solution of the present invention is to provide a method for preparing 1.2GPa grade hydrogen embrittlement resistant cold-formed automobile steel, which is characterized by comprising the following steps: electric furnace smelting, continuous casting and rolling of medium and thin slabs, pickling and cold rolling, quenching and partitioning continuous annealing or continuous hot-dip galvanizing / galvanized aluminum-magnesium or alloyed hot-dip galvanizing, and skin pass.

[0027] The specific steps of the preparation process are as follows:

[0028] Electric furnace smelting: The present invention selects 30% to 70% scrap steel as raw material, and smelts it in an electric furnace to obtain molten steel that meets the following composition requirements by mass percentage: C: 0.20% to 0.30%, Mn: 2.0% to 3.5%, Si: 0.5% to 2.5%, Al: 0.7% to 7.0%, Ni: 0.05% to 0.80%, Mo: 0.05% to 0.80%, P≤0.01%, S≤0.01%, N≤0.005%, Mg: 0.005% to 0.50%, Ti: 0.01% to 0.50%, V: 0.01% to 0.50%, and 5≤Al / Si≤10, 5≤Mo / Ti≤10; the remainder is Fe and unavoidable impurities. The temperature of the molten steel is between 1600 and 1750°C.

[0029] Continuous casting and rolling of medium and thin slabs: using special protective slag for high aluminum steel (Li 2 The hot rolled coil is casted with a content of 0.5% to 10.0% (O content ranges from 0.5% to 10.0%), the casting temperature is between 1530 and 1600°C, the casting machine pulling speed is 1.0 to 5.5 m / min, and the continuous casting billet thickness is between 60 and 115 mm. The starting rolling temperature is between 1000 and 1150°C, the final rolling temperature is above 900°C, and the coiling temperature is between 600 and 700°C. The hot rolled coil thickness specification is 2.0 to 4.5 mm, and the hot rolled microstructure is composed of 30% to 60% (volume ratio) ferrite, 20% to 50% (volume ratio) pearlite, 5% to 20% (volume ratio) bainite, and 1% to 5% cementite; the total is 100%.

[0030] Pickling cold rolling: Before cold rolling, the hot rolled steel coil is treated with acid to remove the surface iron oxide scale, and the cold rolling reduction rate is 45% to 70%. If the reduction rate is too high, the deformation resistance will be too large, and it will be difficult to roll to the target thickness; if the reduction rate is too low, the elongation of the cold rolled steel plate will decrease. The thickness of the finished product after cold rolling is 1.0mm to 2.0mm.

[0031] Continuous annealing with quenching and partitioning: belt speed is controlled at 60-150m / min, furnace temperature in the soaking section is 760-880℃, soaking time is 20-600s, slow cooling outlet temperature is 700-750℃, rapid cooling rate is greater than 50℃ / s, rapid cooling temperature is between 100-250℃, partitioning temperature is 250-450℃, and partitioning time is 60-1000s. The soaking temperature is 760-880℃. If the soaking temperature is too high, the ductility of the steel will be reduced due to the complete austenitization and insufficient ferrite ratio; if the soaking temperature is too low, the soft phase ferrite ratio of the final material will be too high, which will greatly reduce the strength of the material. The soaking time is 30-300s. If the soaking time is too long, the steel plate will have coarse grains. If the annealing time is too short, the steel plate will not have time to complete the annealing and recrystallization process, resulting in a decrease in the elongation of the steel plate.

[0032] Continuous hot-dip galvanizing / galvanized aluminum-magnesium with quenching and partitioning: belt speed is controlled at 60-150m / min, annealing temperature is between 760-880℃, dew point temperature is controlled between -20--10℃, annealing time is between 30-300s, slow cooling outlet temperature is 680-750℃, rapid cooling rate is greater than 40℃ / s, rapid cooling outlet temperature is 150-250℃, galvanizing temperature is 450-470℃, after galvanizing, the strip is first cooled to 400-420℃ by air knife, then cooled by air, and the top roller temperature of the cooling tower is controlled at 250-300℃. The composition of the galvanizing bath contains 0.16%-0.25% Al, the rest is Zn and unavoidable impurities, and the weight of the zinc layer per unit area is 60-200g / cm 2 The zinc-aluminum-magnesium plating solution contains 2.0% to 10.0% Al, 1.0% to 5.0% Mg, 0.001% to 0.1% Si, and the rest is Zn and unavoidable impurities. The weight of the zinc-aluminum-magnesium coating per unit area is 50 to 200 g / cm 2 .

[0033] Quenching and alloying hot-dip galvanizing: the strip speed is controlled at 60-150m / min, the annealing temperature is 770-870℃, the annealing time is between 30 and 300s, the dew point is controlled at -20--10℃, the slow cooling outlet temperature is 680-750℃, the rapid cooling rate is greater than 40℃ / s, the rapid cooling outlet temperature is between 150 and 250℃, the galvanizing temperature is 450-470℃, after galvanizing, the strip is first air-knife cooled to 400-420℃, and then alloying treatment is carried out, the alloying temperature is 470-530℃, and the alloying holding time is 5-60s.

[0034] Skin finishing: The skin finishing process adopts rolling force control, the rolling force is controlled at 1000-3500kN, and the rolling tension is 500~2000kN.

[0035] The microstructure of the 1.2GPa-grade hydrogen embrittlement-resistant cold-formed automobile steel plate prepared by the present invention is 10% to 30% ferrite, 60% to 80% martensite, and 5% to 20% residual austenite, the total of which is 100%; the residual austenite is in a film-like form, with a grain size between 0.05μm and 0.50μm, and the film-like residual austenite is mainly distributed between the martensite laths.

[0036] The beneficial effects of the present invention are:

[0037] (1) The chemical composition of the steel material of the present invention mainly includes C, Mn, Al and Si as the main elements, and the initial cost is relatively low. The present invention adopts a new short-process low-cost production process of "large proportion of scrap steel + electric furnace smelting + medium and thin slab continuous casting and rolling", which can greatly reduce carbon emissions and save energy consumption;

[0038] (2) The 1.2GPa-grade hydrogen embrittlement-resistant cold-formed automobile steel produced by the present invention can add a large amount of aluminum elements to achieve low-density high-strength steel, meeting the requirements of lightweight automobile design;

[0039] (3) The 1.2GPa-grade hydrogen embrittlement-resistant cold-formed automobile steel produced by the present invention can realize a set of alloy systems to meet the diversified product requirements of 1.2GPa-grade quenching and partitioning steel continuous annealing, continuous hot-dip galvanizing / galvanized aluminum-magnesium and alloyed hot-dip galvanizing, etc., due to the special design of composition and process, that is, one steel can be used for multiple purposes, which can not only greatly shorten the product development cycle and R&D costs, but also realize the conversion between multiple grades of products and significantly improve product production efficiency, meeting the energy-saving, environmental protection and green transformation and development of automobile steel;

[0040] (4) The 1.2 GPa grade hydrogen embrittlement resistant cold-formed automobile steel produced by the present invention can achieve a steel yield strength ≥ 900 MPa, a tensile strength ≥ 1200 MPa, an A80 elongation after fracture ≥ 16.0%, a hole expansion rate ≥ 30%, and a density of 6.5 to 7.5 g / cm3; it adopts 180° U-shaped bending to pre-stress and is immersed in a 0.5 mol / L HCl solution for 14 days without delayed fracture, showing excellent performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is the typical microstructure of Example 1-1 of the present invention.

[0042] Figure 2 This is a typical microstructure of Example 1-2 of the present invention.

[0043] Figure 3 It is a typical microstructure of Examples 1-3 of the present invention.

[0044] Figure 4 It is a typical microstructure of Examples 1-4 of the present invention.

[0045] Figure 5 This is a typical engineering stress-strain curve of Example 1-1 of the present invention. DETAILED DESCRIPTION

[0046] The present invention will be further described below by way of examples.

[0047] According to the component ratio of the technical solution, the embodiment of the present invention carries out smelting, continuous casting and rolling of medium and thin slabs, pickling and cold rolling, quenching and distribution, and skin finishing.

[0048] Continuous casting and rolling of medium and thin slabs

[0049] High aluminum steel special protective slag is used for casting. 2O content ranges from 0.5% to 10.0%, casting temperature is 1530-1600℃, casting machine pulling speed is 1.0-5.5m / min, continuous casting billet thickness is between 60-115mm. The starting rolling temperature is between 1000-1150℃, the final rolling temperature is above 900℃, and the coiling temperature is between 600-700℃. The hot rolled coil thickness specification is 2.0-4.5mm;

[0050] Pickling cold rolling

[0051] Before cold rolling, the hot rolled steel coil is passed through an acid solution to remove the surface iron oxide scale, and the cold rolling reduction rate is 45% to 70%;

[0052] Quenching distribution

[0053] The quenching distribution is one of quenching distribution continuous annealing, quenching distribution continuous hot-dip galvanizing or galvanized aluminum-magnesium, and quenching distribution alloying hot-dip galvanizing;

[0054] Skin finishing: The skin finishing process adopts rolling force control, the rolling force is controlled at 1000-3500kN, and the rolling tension is 500~2000kN.

[0055] Furthermore, the quenching and partitioning process is a quenching and partitioning continuous annealing, the belt speed is controlled at 60-150 m / min, the furnace temperature of the soaking section is 760-880°C, the soaking time is 20-600s, the slow cooling outlet temperature is 700-750°C, the rapid cooling rate is greater than 50°C / s, the rapid cooling temperature is between 100-250°C, the partitioning temperature is 250-450°C, and the partitioning time is 60-1000s.

[0056] Furthermore, the quenching and matching process is quenching and matching continuous hot-dip galvanizing or galvanized aluminum-magnesium, the belt speed is controlled at 60-150 m / min, the annealing temperature is between 760 and 880°C, the dew point temperature is controlled between -20 and -10°C, the annealing time is between 30 and 300s, the slow cooling outlet temperature is 680-750°C, the rapid cooling rate is greater than 40°C / s, the rapid cooling outlet temperature is 150-250°C, the galvanizing temperature is 450-470°C, and after galvanizing, the strip is first air-knife cooled to 400-420°C, and then air-cooled, and the temperature of the cooling tower top roller is controlled at 250-300°C.

[0057] Furthermore, the zinc plating solution contains 0.16% to 0.25% Al, the rest is Zn and unavoidable impurities, and the weight of the zinc layer per unit area is 60 to 200 g / cm 2 The zinc-aluminum-magnesium plating solution contains 2.0% to 10.0% Al, 1.0% to 5.0% Mg, 0.001% to 0.1% Si, and the rest is Zn and unavoidable impurities. The weight of the zinc-aluminum-magnesium coating per unit area is 50 to 200 g / cm2 .

[0058] Furthermore, the quenching and partitioning process is quenching and partitioning alloying hot-dip galvanizing, the strip speed is controlled at 60-150 m / min, the annealing temperature is 770-870°C, the annealing time is 30-300s, the dew point is controlled at -20--10°C, the slow cooling outlet temperature is 680-750°C, the rapid cooling rate is greater than 40°C / s, the rapid cooling outlet temperature is 150-250°C, the galvanizing temperature is 450-470°C, and after galvanizing, the strip is first air-knife cooled to 400-420°C, and then alloying treatment is carried out, the alloying temperature is 470-530°C, and the alloying holding time is 5-60s.

[0059] Furthermore, the electric furnace smelting process uses 30% to 70% scrap steel as raw material, and the temperature of the molten steel is 1600 to 1750°C.

[0060] The present invention is described in more detail by way of examples. These examples are merely descriptions of the best mode for carrying out the present invention and do not limit the scope of the present invention in any way.

[0061] The composition of the steel of the embodiment of the present invention is shown in Table 1. The main process parameters of smelting and continuous casting and rolling and the hot rolling structure of the steel of the embodiment of the present invention are shown in Table 2. The main process parameters of continuous annealing and the microstructure of the steel of the embodiment of the present invention are shown in Table 3. The main process parameters of continuous hot-dip galvanizing and the microstructure of the steel of the embodiment of the present invention are shown in Table 4. The main process parameters of continuous hot-dip galvanizing and aluminum-magnesium galvanizing and the microstructure of the steel of the embodiment of the present invention are shown in Table 5. The main process parameters of alloying hot-dip galvanizing and the microstructure of the steel of the embodiment of the present invention are shown in Table 6. The properties of the steel of the embodiment of the present invention are shown in Table 7. The microstructure composition of the steel of the embodiment of the present invention is shown in Table 8.

[0062] Table 1 Chemical composition of example steel (wt%)

[0063] Example C Mn Si Al Ni Mo P S N Mg Ti V Al / Si Mo / Ti 1 0.23 2.34 0.63 4.33 0.23 0.41 0.001 0.005 0.004 0.014 0.059 0.057 6.87 6.95 2 0.21 2.26 0.77 3.92 0.41 0.35 0.005 0.003 0.001 0.027 0.041 0.066 5.09 8.54 3 0.25 2.47 0.82 6.81 0.32 0.63 0.001 0.001 0.001 0.141 0.092 0.31 8.30 6.85 4 0.24 2.15 0.96 5.12 0.55 0.72 0.003 0.002 0.001 0.225 0.12 0.032 5.33 6.00 5 0.22 2.36 0.64 4.45 0.43 0.64 0.002 0.001 0.002 0.084 0.11 0.25 6.95 5.82 6 0.26 2.74 1.08 6.89 0.11 0.28 0.002 0.005 0.003 0.304 0.032 0.17 6.38 8.75

[0064] Table 2 Smelting and continuous casting and rolling process parameters and hot rolling structure of example steel

[0065]

[0066]

[0067] Table 3 Continuous annealing process and microstructure of example steel

[0068]

[0069] Table 4 Main process parameters and microstructure of continuous hot-dip galvanizing of steel in the embodiment of the present invention

[0070]

[0071] Table 5 Main process parameters and microstructure of continuous hot-dip galvanized aluminum-magnesium steel in the embodiment of the present invention

[0072]

[0073] Table 6 Main process parameters and microstructure of hot-dip galvanizing of steel in the embodiment of the present invention

[0074]

[0075] Table 7 Properties of steel according to the present invention

[0076]

[0077]

[0078] Note: The hydrogen embrittlement resistance (delayed fracture resistance) performance is evaluated by U-bending immersion evaluation. The radius of 180° cold bending is 5mm. Five parallel specimens in each group are immersed in 0.5mol / L HCl solution for 14 days. If no fracture occurs, it is judged that the specimen has no delayed fracture risk and is marked with Ο; if fracture occurs, it is judged that the specimen has delayed fracture risk and is marked with ×.

[0079] Table 8 Microstructure of steel according to the present invention

[0080]

[0081]

[0082] It can be seen from the above embodiments that the composition design of the present invention, large proportion of scrap steel + electric furnace smelting, continuous casting and rolling, quenching and partitioning continuous annealing or continuous hot-dip galvanizing / galvanized aluminum-magnesium or alloyed hot-dip galvanizing process, is used to prepare 1.2GPa grade hydrogen embrittlement resistant cold-formed automobile steel with a yield strength of ≥900MPa, a tensile strength of ≥1200MPa, an A80 elongation after fracture of ≥16.0%, a hole expansion rate of ≥30%, and a density of 6.5-7.5g / cm 3 ; The pre-stress was set by 180° U-shaped bending and immersed in 0.5mol / LHCl solution for 14 days, but no delayed fracture occurred; it meets the requirements of automobiles for delayed fracture resistance, high strength and high plasticity, and excellent forming performance.

[0083] In order to describe the present invention, the present invention is appropriately and fully illustrated by the examples in the above. The above implementation modes are only used to illustrate the present invention, but not to limit the present invention. Ordinary technicians in the relevant technical field can make various changes and modifications without departing from the spirit and scope of the present invention. Any modifications, equivalent substitutions, improvements, etc. made should be included in the protection scope of the present invention. The patent protection scope of the present invention should be defined by the claims.

Claims

1. A 1.2GPa grade hydrogen embrittlement resistant cold-formed automotive steel. It is characterized in that By weight percentage, it is composed of the following components: C: 0.20%~0.30%, Mn: 2.0%~3.5%, Si: 0.5%~2.5%, Al: 3.92%~7.0%, Ni: 0.05%~0.80%, Mo: 0.63%~0.8%, P≤0.01%, S≤0.01%, N≤0.005%, Mg: 0.014%~0.5%, Ti: 0.11%~0 .5%, V: 0.17%~0.5%, the balance is Fe and inevitable impurities; the microstructure of the automobile steel is, by volume percentage, 10%~30% ferrite, 60%~80% martensite, 5%~20% retained austenite, the total of which is 100%; the retained austenite is in a film-like morphology, the grain size is between 0.05µm~0.50µm, and the film-like retained austenite is mainly distributed between the martensite laths.

2. The 1.2 GPa grade hydrogen embrittlement resistant cold-formed automobile steel according to claim 1, It is characterized in that The composition includes 5≤Al / Si≤10, 5≤Mo / Ti≤6.95 。 3. The 1.2 GPa grade hydrogen embrittlement resistant cold-formed automobile steel according to claim 1, It is characterized in that The yield strength of the automobile steel is ≥900MPa, the tensile strength is ≥1200MPa, 80 Elongation after fracture ≥16.0%, hole expansion rate ≥30%, density 6.5~7.5 g / cm 3 The automobile steel was prestressed by 180° U-bending and immersed in a 0.5 mol / L HCl solution for 14 days without delayed fracture; the automobile steel had a thickness of 1.0 mm to 2.0 mm.

4. A method for manufacturing a 1.2 GPa grade hydrogen embrittlement resistant cold-formed automobile steel according to any one of claims 1 to 3, comprising smelting, continuous casting and rolling of medium and thin slabs, pickling and cold rolling, quenching and partitioning, and skin-passing. It is characterized in that Continuous casting and rolling of medium and thin slabs: High aluminum steel special protective slag is used for casting. 2 The O content ranges from 0.5% to 10.0%, the casting temperature is between 1530 and 1600°C, the casting speed is 1.0 to 5.5 m / min, and the continuous casting billet thickness is between 60 and 115 mm; The starting rolling temperature is between 1000~1150℃, the final rolling temperature is above 900℃, the coiling temperature is between 600~700℃, and the hot rolled coil thickness specification is 2.0~4.5mm; Pickling and cold rolling: Before cold rolling, the hot rolled steel coil is passed through acid solution to remove the surface iron oxide scale, and the cold rolling reduction rate is 45%~70%; Quenching distribution: The quenching distribution is one of quenching distribution continuous annealing, quenching distribution continuous hot-dip galvanizing or galvanized aluminum-magnesium, and quenching distribution alloying hot-dip galvanizing; Skin finishing: The skin finishing process adopts rolling force control, the rolling force is controlled between 1000~3500kN, and the rolling tension is 500~2000kN.

5. The method for manufacturing a 1.2 GPa grade hydrogen embrittlement resistant cold-formed automobile steel according to claim 4, It is characterized in that The quenching and partitioning process is quenching and partitioning continuous annealing, the belt speed is controlled between 60 and 150 m / min, the furnace temperature of the soaking section is 760 to 880°C, the soaking time is 20 to 600 s, the slow cooling outlet temperature is 700 to 750°C, the rapid cooling rate is greater than 50°C / s, the rapid cooling outlet temperature is between 100 to 250°C, the partitioning temperature is between 250 to 450°C, the partitioning time is between 60 to 1000 s, the soaking temperature is 760 to 880°C, and the soaking time is 30 to 300 s.

6. The method for manufacturing a 1.2 GPa grade hydrogen embrittlement resistant cold-formed automobile steel according to claim 4, It is characterized in that The quenching and partitioning process is quenching and partitioning continuous hot-dip galvanizing or galvanized aluminum-magnesium, the belt speed is controlled between 60 and 150 m / min, the annealing temperature is between 760 and 880°C, the dew point temperature is controlled between -20 and -10°C, the annealing time is between 30 and 300s, the slow cooling outlet temperature is 680 to 750°C, the rapid cooling rate is greater than 40°C / s, the rapid cooling outlet temperature is 150 to 250°C, the galvanizing temperature is 450 to 470°C, and after galvanizing, the strip is first air-knife cooled to between 400 and 420°C, and then air-cooled, and the temperature of the cooling tower top roller is controlled between 250 and 300°C.

7. The method for manufacturing a 1.2 GPa grade hydrogen embrittlement resistant cold-formed automobile steel according to claim 6, It is characterized in that The zinc plating solution consists of the following components by weight percentage: Al: 0.16% to 0.25%, the rest is Zn and unavoidable impurities, and the weight of the zinc layer per unit area is 60 to 200 g / cm 2 The zinc-aluminum-magnesium plating solution is composed of the following components: Al: 2.0%~10.0%, Mg: 1.0%~5.0%, Si: 0.001%~0.1%, and the rest is Zn and unavoidable impurities. The weight of the zinc-aluminum-magnesium coating per unit area is 50~200g / cm 2 .

8. The method for manufacturing a 1.2 GPa grade hydrogen embrittlement resistant cold-formed automobile steel according to claim 4, It is characterized in that The quenching and partitioning process is quenching and partitioning alloying hot-dip galvanizing, the strip speed is controlled between 60 and 150 m / min, the annealing temperature is 770 to 870°C, the annealing time is between 30 and 300 s, the dew point is controlled between -20 and -10°C, the slow cooling outlet temperature is 680 to 750°C, the rapid cooling rate is greater than 40°C / s, the rapid cooling outlet temperature is between 150 and 250°C, the galvanizing temperature is 450 to 470°C, and after galvanizing, the strip is first air-knife cooled to between 400 and 420°C, and then alloying treatment is performed, the alloying temperature is 470 to 530°C, and the alloying holding time is 5 to 60s.

9. The method for manufacturing a 1.2 GPa grade hydrogen embrittlement resistant cold-formed automobile steel according to claim 4, It is characterized in that The hot-rolled microstructure of the hot-rolled process is composed of 30% to 60% ferrite, 20% to 50% pearlite, 5% to 20% bainite, and 1% to 5% cementite by volume percentage, and the total is 100%.